Net-Zero Energy Reformation in Urban Planning and Building: The IKN Case Study - Rachmanda, Resinthia (RUAS, 2025)
The Indonesian government initiated the establishment of Ibu Kota Negara (IKN), relocating Indonesia’s capital to East Kalimantan to address the unsustainable and uneven existing urban development, along with the impacts of climate change issues. As the first city in the country to be built from scratch, IKN represents an opportunity to pioneer a sustainable environment by adopting Net Zero Energy (NZE) standards. The scope of this paper is limited to discussing city planning and the green building sector. This study employs a descriptive qualitative method based on literature review to analyze the evolution of urban development policies in Indonesia towards Net Zero Energy (NZE) standards on the development of IKN. Furthermore, this paper focuses on the government’s efforts to transform from previous policies to the NZE framework through public sector reforms, policy and regulation reform, implementation, and challenges. It also delves into the early stages of NZE adoption on a national scale within Indonesia's unique socio-political context. The IKN serves as a pilot project for achieving NZE, its success is crucial not only for demonstrating the feasibility of NZE nationwide. Hence, the execution of IKN should be neutral and free from any political intentions to ensure its citizen-centric purpose is not obscured.